Anticardiolipin antibodies and 12-month graft function in kidney transplant recipients: a prognosis cohort survey. Issue 4 (16th January 2018) - Gauthier, Marion; Canoui-Poitrine, Florence; Guéry, Esther; Desvaux, Dominique; Hue, Sophie; Canaud, Guillaume; Stehle, Thomas; Lang, Philippe; Kofman, Tomek; Grimbert, Philippe; Matignon, Marie
Abstract: Background: In kidney transplant recipients, anticardiolipin (ACL) antibodies without antiphospholipid syndrome (APS) are found in up to 38% of patients and could be associated with thrombotic events (TEs). However, the prognostic role of ACL regarding kidney transplant and patients outcomes have still not been well defined. Methods: We conducted an observational, monocentric, retrospective cohort study including 446 kidney transplant recipients and standardized follow-up: 36-month allograft and patient survival, 12-month estimated glomerular filtration rate (eGFR) and 3- and 12-month screening biopsies. Results: ACL tests were run on 247 patients, 101 were positive (ACL+ group, 41%) and 146 were negative (ACL– group, 59%). Allografts and patient survival within 36 months as TE were similar between both groups [hazard ratio (HR) = 1.18 and HR = 0.98, respectively]. The 12-month eGFR was significantly lower in the ACL+ group [median (95% confidence interval) 48.5 (35.1–60.3) versus 51.9 (39.1–65.0) mL/min/1.73 m 2, P= 0.042]. ACL+ was independently associated with eGFR decrease (P = 0.04). In 12-month screening biopsies, tubular atrophy was significantly more severe in the ACL+ group compared with the ACL− group (P = 0.02). Conclusions: ACL without APS before kidney transplantation is an independent risk factor of eGFR decline within the first year post-transplant without over-incidence of TEs. Specific immunosuppressive therapy including mammalian target of rapamycin inhibitors should be discussed in the future.